Using of Personal Protection Equipment in Dental Policlinic of Dental Nurses Based on Knowledge Level About Infection Desease - Nova Herawati; Fitri Agusni; Ika Ifitri (Faculty of Public Health, Andalas University, 2017)
DentalÂ health workers have a high risk infection because the presence of pathogenic microorganisms in the oral cavity including blood and saliva and possibility of injury caused by needle stick. Transmission of infection can be prevented by reducing contact with cause of infection one of them with the use of self-protection tool in according â€œStandard Operational Procedureâ€. The study aim is to know the Knowledge of Dental Nurses about Infectious Diseases against the Use of Personal Protection Equipment in Dental Policlinic of Puskesmas in Bukittinggi and Payakumbuh. By using â€œCross Sectionalâ€ design. Population was used all dental nurse at Dental Clinic amount 30 peoples. By using total population and data collection using questionnaire and observation. The results is a positive relationship and stronger between the knowledge of dental nurse about infection diseases of the using self-protection tool with r value in the amount of 0,886 (Î± 0,00 < 0,05). The conclusion is the higher knowledge of dental nurses about infectious diseases will be more complete and appropriate SOP. Suggested can be increasing their knowledge about infectious disease so that can protect him self one of them with the use of self-protection equipment according to SOP before and during the action.